1998
DOI: 10.1159/000054376
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Secretion of Gonadotropin-Releasing Hormone (GnRH) and [Hydroxyproline<sup>9</sup>]GnRH from the Rat Hypothalamus Exhibits a Differential Sensitivity to Castration and Second Messengers

Abstract: The decapeptide [hydroxyproline9]GnRH (HypGnRH) has been characterized as an endogenous posttranslational product of the gonadotropin-releasing hormone (GnRH) precursor in a wide range of mammalian brains. Despite consistent biological effects, its secretion by the hypothalamus remains hypothetical. We report here in vitro secretion of HypGnRH and GnRH by the hypothalamus from intact and castrated male rats and provide evidence that they are differentially regulated. Both peptides were identified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1

Year Published

2000
2000
2005
2005

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 50 publications
(77 reference statements)
1
15
1
Order By: Relevance
“…It is reported that [Hyp 9 ]GnRH is released from the hypothalamus by different mechanisms in adult [39]and developing rats [40]and can potentially act on the secretion of human chorionic gonadotropin secretion from perifused placental cells [41]. Nevertheless, its actions are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that [Hyp 9 ]GnRH is released from the hypothalamus by different mechanisms in adult [39]and developing rats [40]and can potentially act on the secretion of human chorionic gonadotropin secretion from perifused placental cells [41]. Nevertheless, its actions are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were performed with the same weight of tissue (0.9–1.1 g) for each postnatal day examined. Preparation of tissues has been previously reported ( 2). Briefly, for one experiment, 15–60 tissues (according to the postnatal period examined) were mixed and placed into a single plastic flask (35 × 25 mm) positioned in a water bath (37 °C) under constant shaking.…”
Section: Methodsmentioning
confidence: 99%
“…We recently reported the in vitro cosecretion of gonadotropin‐releasing hormone (GnRH) and its hydroxylated molecular form, [hydroxyproline 9 ]GnRH (HypGnRH) ( 1) from the whole hypothalamus of adult intact and castrated male rats ( 2). Release of the two forms of GnRH was shown to be differentially regulated after either membrane depolarization or activation of different signalling pathways involving adenylate cyclase, protein kinases A and C (PKA, PKC).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…But, in addition to a previous study [34], we established here that both decapeptides are present at an early developmental stage in association with some of their catabolites and precursors which have been already identified in the adult animals [15, 16] and in the GT1 cell line [35, 36]. The chromatography of large amounts of tissues and the use of two combined HPLC steps made it possible to detect these additional metabolic compounds which mostly coelute with mHypGnRH or mGnRH on a single RP-HPLC [37]. Our data confirm that the hypothalamic GnRH-like content increased with advancing age in both sexes, reaching higher amounts in males than in females [38].…”
Section: Discussionmentioning
confidence: 99%